Acute hematological response to a single dose of sprint interval training in competitive cyclists - Hebisz, P.; Hebisz, R.; Bakonska-Pacon, E.; Zaton, M. (Science & Sports, 2017)
Objectives: The purpose of the study was to evaluate the acute hematological response to a sprint interval testing protocol in cyclists. Methods: Sixteen cyclists executed 4 sets of maximal intensity cycling separated by 20-40min active recovery. Each set involved four 30s maximal sprints interspersed with 90s low-intensity recovery. Power output was recorded. Red and white blood cell, hemoglobin, and hematocrit levels were obtained at baseline and 2min after each set. Percentage change in plasma volume was calculated. Body composition and mass were measured pre- and post-sprint interval testing protocol. Results: Power output was maintained at similar level throughout all sets of exercise. Respective increases compared with baseline were observed in each consecutive set for red blood cell (by 8.4%, 6.8%, 5.6%, 3.8%), white blood cell (by 107.8%, 119.6%, 284.3%, 339.2%), hemoglobin (by 7.5%, 6.1%, 4.1%, 2.0%), and hematocrit (by 9.2%, 7.5%, 7.0%, 3.7%). There was a reduction in plasma volume (by -14.5%, -11.7%, -9.2%, -5.4%) compared with baseline. Body mass and water content decreased post- sprint interval testing protocol. Conclusions: While sprint interval testing protocol induced acute hypovolemia, the magnitude difference progressively decreased with consecutive sets of exercise, suggesting plasma volume expansion during active recovery between-sets. Significant white blood cell increases in subsequent sets of maximal exercise suggests an inflammatory response and may hinder microcirculation.